Pengaruh Persepsi dan Motivasi Wisatawan Domestik Terhadap Keputusan Berkunjung Kembali di Taman Hutan Raya Ir. H. Djuanda (Tahura) Bandung - Mulyana, Hadi (Manajemen dan Pariwisata, 2025)
This study aims to determine the effect of perceptions on the decision to visit Taman Hutan Raya Ir. H. Juanda Bandung, to determine the influence of motivation on the decision to revisit tourists at Taman Hutan Raya, Ir. H. Juanda Bandung, and to determine the effect of perceptions and motivation on visiting decisions. Back tourists Taman Hutan Raya Ir. H. Juanda Bandung. In this research, the type and research method used is descriptive and verification with a quantitative approach. The population of this study were 100 tourists who had visited Taman Hutan Raya Ir. H. Juanda Bandung. The results of the research on the F test show that the variables of perception and motivation together or simultaneously have a positive effect on the variable of the decision to return to Taman Hutan Raya Ir. H. Juanda Bandung. The T test shows that the perception variable has a positive effect on the variable of the decision to return to the Forest Park Ir. H. Juanda Bandung. And the motivation variable has a positive effect on the variable of the decision to return to the Forest Park Ir. H. Juanda Bandung.